2016
DOI: 10.17267/2238-2720revbahianaodonto.v7i1.706
|View full text |Cite
|
Sign up to set email alerts
|

Influência Do Uso De Bisfosfonatos Em Pacientes Submetidos a Implantes Dentários: Revisão Da Literatura

Abstract: ResumoO uso de implantes dentários como alternativa reabilitadora em pacientes com necessidade de restabelecimento do sistema estomatognático através da reposição das unidades dentárias é uma prática cada vez mais comum. Desafios sobre o manejo dos pacientes que apresentam algum fator adicional para a prática das reabilitações dentárias com implantes é uma constante, principalmente aquelas descritas na literatura acerca do insucesso envolvendo uso de fármacos à base de bisfosfonatos, sendo apontado diretamente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(33 reference statements)
0
1
0
1
Order By: Relevance
“…Studies have reported that the oral use of bisphosphonates has a low risk of osteonecrosis, although there are cases reported in the literature ( Kishimoto et al, 2019 ). Nevertheless, there is evidence that the duration of pharmacological treatment with these drugs is decisive, considering that there is no benefit in suspension when the treatment exceeds 3 years of continuous use ( Santos et al, 2016 , Mendes et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the oral use of bisphosphonates has a low risk of osteonecrosis, although there are cases reported in the literature ( Kishimoto et al, 2019 ). Nevertheless, there is evidence that the duration of pharmacological treatment with these drugs is decisive, considering that there is no benefit in suspension when the treatment exceeds 3 years of continuous use ( Santos et al, 2016 , Mendes et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Procedimentos odontológicos mais comuns e invasivos como extrações dentárias (Souza Junior et al, 2020) e instalação de implantes dentários (Leite et al, 2015;Santos et al, 2016) devem ser planejados e executados de forma criteriosa e ponderar a real necessidade de sua realização (Chaves et al, 2018;Stramandinoli-Zanicotti et al, 2018), especialmente antes de iniciar o tratamento com bisfosfonatos. Quando sua execução for imperativa, exames laboratoriais pré-operatórios como a dosagem do Telopeptídeo-C Terminal ou colágeno tipo I (CTX), marcadores específicos da reabsorção óssea liberados durante a remodelação e renovação óssea, podem auxiliar no planejamento e sugerir risco de ocorrência de osteonecrose pósoepratória.…”
unclassified